Self-Awareness as Part of Socio-Emotional Learning and its Implications on Academic Achievement among O-level Students in Secondary Schools in Kyabugimbi Sub County, Uganda - Musinguzi, Alexson Bukenyo; Aheisibwe, Irene; Ahabwe, Emmanuel (East African Journal of Education Studies, 2024)
Introduction: Academic achievement is one of the most important variables in determining educational outcomes and success outside of school. This study is about the relationship between self-awareness as part of socio-emotional learning and its implications on students’ academic achievement among O-level students in secondary schools in Kyabugimbi Sub County. Objectives: The study sought to examine the relationship between self-awareness and students’ academic achievement among O-level students in secondary schools in Kyabugimbi Sub County. Methodology: A cross-sectional study design was used where data was collected at a single point in time. The study population comprised of 2,682 students in S1-S3 in six secondary schools in Kyabugimbi Sub County. The sample size comprised of 235 students. Data was collected using a self-administered close-ended questionnaire and analyzed by generating inferential statistics. Findings: The study findings show a strong positive significant relationship (r=0.681**; p<0.05) between self-awareness and students’ academic achievement among O-level students in secondary schools. Conclusions and recommendations: The study concludes that self-awareness is one of the critical aspects for socio-emotional learning that play a significant role towards the students’ academic achievement. The study recommends policymakers to prioritize self-awareness programs in schools, integrating self-awareness activities into the school curriculum, training teachers to help students develop self-awareness and educating parents on fostering the importance of self-awareness needs of their children at home